The Intestinal Dysbiosis of Mothers with Gestational Diabetes Mellitus (GDM) and Its Impact on the Gut Microbiota of Their Newborns. (22nd September 2021) - Li, Xinke; Yu, Da; Wang, Yushuang; Yuan, Huimin; Ning, Xixi; Rui, Binqi; Lei, Zengjie; Yuan, Jieli; Yan, Jingyu; Li, Ming
Abstract : Gestational diabetes mellitus (GDM) is defined as "diagnosed as impaired glucose tolerance for the first time during pregnancy, " which can lead to adverse pregnancy outcomes and produces divergent effects on mothers and newborns. In recent years, with the continuous expansion of obese people, GDM shows an upward trend. The abundant and diverse members of the human gut microbiota exert critical roles in the maintenance of human health. Studies have shown that GDM may be associated with disordered gut microbiota in both mothers and newborns. Taking into account the potential effects on maternal and consequently neonatal health, in this review, we analyzed the available data and discussed the current knowledge about the potential relationship between GDM and intestinal dysbiosis in mothers and newborns. In addition, we also discussed the influencing factors derived from GDM mothers on the gut microbiome of their newborns, including the vertical transmission of microbiota from mothers, the alteration of milk components of GDM mothers, and using of probiotics. Hoping that new insights into the role of the gut microbiota in GDM could lead to the development of integrated strategies to prevent and treat these metabolic disorders.